Early insights into the genome sequence of Uromyces fabae - Link, Tobias; Seibel, Christian; Voegele, Ralf T. (Frontiers in Plant Science, 2014)
Uromyces fabae is a major pathogen of broad bean, Vicia faba. U. fabae has served as a model among rust fungi to elucidate the development of infection structures, expression and secretion of cell wall degrading enzymes and gene expression. Using U. fabae, enormous progress was made regarding nutrient uptake and metabolism and in the search for secreted proteins and effectors. Here, we present results from a genome survey of U. fabae. Paired end Illumina sequencing provided 53 Gb of data. An assembly gave 59,735 scaffolds with a total length of 216 Mb. K-mer analysis estimated the genome size to be 329 Mb. Of a representative set of 23,153 predicted proteins we could annotate 10,209, and predict 599 secreted proteins. Clustering of the protein set indicates families of highly likely effectors. We also found new homologs of RTP1p, a prototype rust effector. The U. fabae genome will be an important resource for comparative analyses with U. appendiculatus and P. pachyrhizi and provide information regarding the phylogenetic relationship of the genus Uromyces with respect to other rust fungi already sequenced, namely Puccinia graminis f. sp. tritici, P. striiformis f. sp. tritici, Melampsora lini, and Melampsora larici-populina.